2017
DOI: 10.5530/ijper.51.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of integrating research skills with basic sciences in an interdisciplinary integrated endocrine module on students’ satisfaction and performance

Abstract: Background: A system-based integrated curriculum has been implemented at Faculty of Medicine, King Abdulaziz University since the academic year 2006/2007. There were many calls to increase the integration level and to integrate the scientific research skills into the medical curriculum. Objectives: This study aimed to document the steps taken to establish a higher level of integration of basic sciences along with the scientific research skills and to assess the effect of such changes on student satisfaction an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…These 40 studies reported integrated educational interventions employed across medicine (n=28) [10-12, 16-21, 23-25, 28, 29, 31, 33, 34, 36, 38-41, 44-49], pharmacy (n=11) [13-15, 26, 27, 29, 30, 32, 35, 37, 42],and dentistry (n=1) [22] in institutions worldwide: United States of America (n=14) [11, 13-15, 24-27, 29, 30, 32, 40, 42, 46], India (n=7) [10, 18-20, 28, 33, 41], United Kingdom (n=6) [22,35,37,39,43], Middle East (n=4) [16,17,23,31], the Netherlands (n=4) [31,44,48,49], Belgium (n=2) [45,47], and one from each of: Stockholm [12], Brazil [21], Germany [36], and Korea [38].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…These 40 studies reported integrated educational interventions employed across medicine (n=28) [10-12, 16-21, 23-25, 28, 29, 31, 33, 34, 36, 38-41, 44-49], pharmacy (n=11) [13-15, 26, 27, 29, 30, 32, 35, 37, 42],and dentistry (n=1) [22] in institutions worldwide: United States of America (n=14) [11, 13-15, 24-27, 29, 30, 32, 40, 42, 46], India (n=7) [10, 18-20, 28, 33, 41], United Kingdom (n=6) [22,35,37,39,43], Middle East (n=4) [16,17,23,31], the Netherlands (n=4) [31,44,48,49], Belgium (n=2) [45,47], and one from each of: Stockholm [12], Brazil [21], Germany [36], and Korea [38].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The number of students experiencing the integrated educational activities was not always described, but where included, cohorts varied from relatively small, approximately 30-40, to very large, approximately 1000-2000 students. Most studies, (n=34) adopted surveys to capture student feedback [10,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][34][35][36][37][38][39][43][44][45][46][47][48][49], six studies employed student interviews or focus groups [11,12,27,29,36,37] and 24 assessed student performance at a terminal assessment [10,14,15,17,18,21,[23]…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations